Determinants of export in Malaysia / Nurul Asyiquin Nordin and Nur Jannah Ramadhan - Nordin, Nurul Asyiquin; Ramadhan, Nur Jannah (Faculty of Business and Management, 2019)
This paper aim at finding out the impact of macroeconomic variables towards economic growth in Malaysia which the export is monitor based on the Export Rate. The variables are considered are exchange rate (ER), foreign direct investment (FDI), economic growth (GDP), unemployment (UNP), and inflation (CPI). This study required 50 years data which is from 1967 until 2017. Methodology used for this study is using Multiple Linear Regression with series data. Thereafter, econometric test is to be conducted to observe the relationship of the independent variables with export. Interactive software package E-view would be used for testing and analyzing the data collected. This study is attempting to investigate there is a significant relationship between the independent variables with the Export and which variables contributes most to export growth. Findings from previous study mostly shows that foreign direct investment, exchange rate, inflation and economic growth has a significant role in the determination of export. As guidance to the past research that have been done, this study will examine the determinants of export in Malaysia.